Using the ADAPT guidance to culturally adapt a brief intervention to reduce alcohol use among injury patients in Tanzania. - Catherine A Staton; Armand Zimmerman; Msafiri Pesambili; Ashley J Phillips; Anna Tupetz; Joao Vitor Perez de Souza; Judith Boshe; Michael H Pantalon; Monica Swahn; Blandina T Mmbaga; Joao Ricardo Nickenig Vissoci (PLOS Global Public Health)
Harmful alcohol use is a leading risk factor for injury-related death and disability in low- and middle-income countries (LMICs). Brief negotiational interventions (BNIs) in emergency departments (EDs) effectively reduce alcohol intake and re-injury rates. However, most BNIs are developed in high-income countries, with limited evidence of their effectiveness in LMICs. To address this gap, we culturally adapted a BNI for alcohol-related injury patients at Kilimanjaro Christian Medical Centre (KCMC), a tertiary hospital in Tanzania. Our study followed the ADAPT guidance to culturally adapt an existing high-income country BNI for use in the KCMC, a tertiary hospital in Tanzania. The adaptation included: 1) a systematic review of effective alcohol harm reduction interventions in similar settings; 2) consultations with local and international healthcare professionals experienced in counseling and substance abuse treatment; 3) group discussions to refine goals and finalize adaptations. The adapted BNI protocol and assessment scales ensured intervention fidelity. At KCMC, 30% of injury patients screened positive for alcohol use disorder (AUD), with a five-fold increased risk of injury, primarily from road traffic accidents and violence. A systematic review highlighted limited data on patient-level interventions in low-resource settings. Our adapted BNI, 'Punguza Pombe Kwa Afya Yako (PPKAY)', based on the FRAMES model, showed high feasibility and acceptability, with 84% of interventions achieving ≥80% adherence and 98% patient satisfaction. PPKAY is the first culturally adapted alcohol BNI for injury patients in an African ED. Our study demonstrates our approach to adapting substance use interventions for use in low resource settings and shows that cultural adaptation of alcohol use interventions is feasible, beneficial and empowering for our team. Our study lays a framework and method for other low resourced settings to integrate cultural adaptation into the implementation of a BNI in low resource EDs.